(untitled) (Journal of the College of Basic Education, 2022)
The city of Mero Rud is one of the important historical cities in the province of Khorasan, as it has had a great impact, like other cities in the region, on the prosperity of cultural life in it and for many centuries. The emergence of scientific houses in the city of Meru al-Rawd had a major impact on the history of the city and other cities of the Islamic world in general and Khurasan in particular. Scientific trips, which are one of the most important elements of the flourishing of intellectual life, helped to increase intellectual cross-fertilization among scholars, as well as scientific councils inside and outside the city. The scholarly feature of many of its scholars, which helped to travel to them from all sides, as in the case of the great scientist Ahmed Ibn Muna`i Al-Marrouthi (Tel: 244 AH / 859AD), who is considered the founder of the Al-Mani’i House in the city of Mrou al-Roud, which had a great role in supporting the movement Scientific in the city and outside A. We discussed through our research after it was divided into three sections: The first topic dealt with a brief summary about the city of Murr al-Rawd and its geography The second topic dealt with the autobiography of Ahmed bin Mune`, may God have mercy on him The second topic we dealt with is the scientific biography of Ahmed bin Mina`, may God have mercy on him